VOLUNTEERING ACTIVITY OF TEENAGERS AS THE BASIS OF VALUE ATTITUDE TO WORK - Коблик, Віталій (Modern engineering and innovative technologies, 2022)
ціннісне ставлення до праці, волонтерська добродійна діяльність, підлітки, позакласна робота, мотивація.